2006
DOI: 10.1111/j.1540-5915.2006.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Information Technology Integration and Lean/Just‐In‐Time Practices on Lead‐Time Performance*

Abstract: Managers seeking to improve lead-time performance are challenged by how to balance resources and investments between process improvement achieved through lean/justin-time (JIT) practices and information technology (IT) deployment. However, extant literature provides little guidance on this question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
179
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(198 citation statements)
references
References 62 publications
12
179
0
7
Order By: Relevance
“…A similar study was conducted amongst 1757 manufacturers to assess the effect of IT integration and lean/just-in-time practices on lead-time performance (Ward and Zhou, 2006). However, results of this study indicated that the customer lead-time was not directly reduced by within-firm IT integration or between-firm IT integration.…”
Section: It Integrationmentioning
confidence: 83%
“…A similar study was conducted amongst 1757 manufacturers to assess the effect of IT integration and lean/just-in-time practices on lead-time performance (Ward and Zhou, 2006). However, results of this study indicated that the customer lead-time was not directly reduced by within-firm IT integration or between-firm IT integration.…”
Section: It Integrationmentioning
confidence: 83%
“…To help clarify the impact of IS integration on firm profitability, we first follow Fayard et al (2012), Bergeron and Raymond (1992), and Ward and Zhou (2006) by categorizing IS integration into two distinct, but closely related, capabilities: internal IS integration and external IS integration. Internal IS integration refers to a firm's electronic links in information technology applications to data acquisition and storage systems that facilitate the sharing of accurate and timely information in support of cross-functional processes (Hammer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Besides mitigating the bullwhip effect and its consequences, information sharing also assists the adoption of lean and just-in-time production (Ward & Zhou, 2006), which prevents disruptions (Chopra & Sodhi, 2004) and promotes agility (White et al, 2005). Businesses are gradually recognising the need agility in today's global economy to be competitive (Pujawan, 2004).…”
Section: Information Sharing and Bullwhip Effectmentioning
confidence: 99%